Profil Antropometri Dan Komposisi Tubuh Pada Siswa Arema Football Academy - Junico Putra Ardianto; Olivia Andiana (LPPM Politeknik Pratama, 2024)
Anthropometrics and body composition are important components in soccer players and are good for supporting player performance. Therefore, this research aims to determine the anthropometric profile and body composition in each position and to determine the differences in anthropometric profile and body composition in each position of Arema Football Academy students. The research method uses a quantitative descriptive research design and an observational approach. The sample used Arema Football Academy students according to the criteria. Then the data was tested using the Anova Test and continued with the Tuckey Test. The results obtained mean that goalkeepers and defenders have the highest average values ​​for height, weight, body mass index according to age and body fat percentage compared to other positions, while the lowest average values ​​are for the midfielder and striker positions. Anova test results, there were significant differences (p = <0.05) in body mass index according to age F = 3.286 (p = 0.27), body weight F = 5.201 (p = 0.03) and body fat percentage F = 4.588 (p = 0.06). Followed by the Tuckey Test with significant results (p = <0.05) between goalkeeper and attacker (p = 0.010) and goalkeeper and midfielder (p = 0.013) on body weight. And goalkeeper with striker (p = 0.005) and goalkeeper with midfielder (p = 0.032) on body fat percentage.